Effect of foot and mouth disease virus infection on hematobiochemical profile in goats under natural conditions (Indian Journal of Veterinary Pathology, 2025)
Foot and mouth disease (FMD) is a contagious viral disease that has a high economic impact on livestock industry affecting large and small ruminant. Most research works are carried out on hematobiochemical alteration due to FMD virus (FMDV) in bovine but there is a paucity of literature and a dearth of research on how FMDV affects the hematobiochemical profiles of goats. This study was aimed to investigate the impact of FMDV on hematobiochemical profile of goats. Forty two whole blood samples were collected from FMDV-infected (n=32) and apparently healthy (n=10) goats to estimate hematobiochemical profile alteration. There was a significant (p